Improving Vietnamese Legal Framework to Ensure the Right to a Fair Trial for Defendants under 18 - Hoa, Nguyen Quang (VNU Journal of Science: Legal Studies; Vol 40 No 2, 2024)
This article provides an overview of the international legal framework and Vietnamese law concerning the right to a fair trial of defendants under 18 years old. It conducts a meticulous comparison of the provisions of Vietnamese law with the relevant international standards, thereby identifying issues of incompatibility of Vietnamese law compared to international law. On this basis, the author highlights limitations and proposes solutions to strengthen Vietnamese law, ensuring a fair trial for defendants under 18.